Obstetric and neonatal outcomes in obese pregnant patients at Aberdeen maternity hospital. (18th April 2012) - Morah, N; Mathur, M; Haque, L
Abstract : Introduction: In 2008 CEMACH concluded the UK prevalence of women with a known BMI ≥35 (Class II and Class III obesity) at any point in pregnancy, giving birth ≥24+0 weeks gestation is 4.99% or 38, 478 maternities each year. Women with a pregnancy BMI ≥40 (Class III obesity) is 2.01%, while super-morbid obesity (BMI ≥50) affects 0.19% of all women giving birth. Risks associated include gestational diabetes mellitus, preeclampsia and venous thromboembolism. Aim: Review of maternity services in AMH for obesity. Methodology: Retrospective case note analysis of 21 patients between January 2009 to July 2009 in women with a BMI of > 40. Results: There were 76% patients identified with a BMI of 40-49, the rest had BMI of 50. Anaesthetic review was achieved by only 67%. Majority of the patients had growth scans (76%) and only 38% had OGTT done. Medical complications identified were GDM in 4%, PET in 19% and PIH in 4% patients. None were diagnosed with VTE, pre or post delivery. Eight patients (38%) were induced, there were 2 elective sections and rest had SOL. Seven patients had LSCS (2 electives and rest emergency), three patients had instrumental deliveries and rest had SVD. 33% had postpartum haemorrhage and 1 women (4%) had wound infection. There was 1 macrosomic baby and 1 NNU admission. Conclusion: Overall the care of the morbidly obese pregnant patients has been reasonably good as reflected both in the obstetric and neonatal outcomes. However we have to be more vigilant in terms of early anaesthetic reviews and antenatal surveillances.